Distribution and Composition of Soil Invertebrates in some Agricultural Fields in Al-Madaain District South Baghdad- Iraq - Al-Waeely, Ghofran Wael; Meshjel, Maysoon Hassan; Al-Zaidawi, Jawad Bulbul (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
Soil invertebrates play an important role in the soil biota community; they are responsible for decomposing, aerating, recycling nutrients, and increasing agricultural products. This study aims to investigate the community of soil invertebrates in the fields of Al-Madaain district in south Baghdad, as well as their correlation with various soil physical and chemical properties. Each field received four randomly selected samples each month. We isolated the invertebrate samples from the soil using two methods: the direct method for large soil invertebrates and the indirect method for small invertebrates. In this study, we included the physical and chemical factors in the soil to determine them (Temperature, Salinity, pH, Organic matter, Humidity, and total calcium). The temperature ranged from 7 to 35 °C, salinity ranged from 0.10 to 6.80 ‰, pH ranged from 6.8 to 8.1, soil organic matter ranged from 0.31 to 7.39%, and total calcium ranged from 50 to 212. The number of isolated invertebrates in the study area was 8407; it belongs to 9 taxa; the most common was terrestrial isopoda (41% of total isolated invertebrates), followed by insects (24%), gastropods (17%), and nematodes (8% of total isolated invertebrates), in addition to earthworms, arachnida, chilopoda, and diplopoda. This study used biological indices such as Shannon-Wiener, uniformity, Jaccard, and richness, as well as the LSD test, to calculate significant differences.